2001
DOI: 10.1073/pnas.251542798
|View full text |Cite
|
Sign up to set email alerts
|

Translation of a nonpolyadenylated viral RNA is enhanced by binding of viral coat protein or polyadenylation of the RNA

Abstract: C ircularization of the genome of RNA viruses plays an essential role in the replication and translation of viral RNAs. Formation of panhandle structures by base pairing between complementary sequences at the 5Ј and 3Јtermini of several genera of minus-strand RNA viruses has been known already for some time (1). Recently, it became clear that cyclization by RNA-RNA interactions may also play an essential role in the replication of positive-strand RNA viruses such as f laviviruses (2, 3). However, for a growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 38 publications
6
77
0
2
Order By: Relevance
“…Neeleman et al (20) reported that coat protein binding may autoregulate AMV RNA translation. This phenomenon would manifest in our experiments if the mutations inserted into genomic RNA 3 or copied into newly transcribed subgenomic coat protein mRNA (i.e., RNA 4) decreased viral RNA replication by reducing viral protein expression as a result of limited viral mRNA translation.…”
Section: Vol 78 2004 Coat Protein Organizes Viral Rna For Replicatimentioning
confidence: 99%
See 1 more Smart Citation
“…Neeleman et al (20) reported that coat protein binding may autoregulate AMV RNA translation. This phenomenon would manifest in our experiments if the mutations inserted into genomic RNA 3 or copied into newly transcribed subgenomic coat protein mRNA (i.e., RNA 4) decreased viral RNA replication by reducing viral protein expression as a result of limited viral mRNA translation.…”
Section: Vol 78 2004 Coat Protein Organizes Viral Rna For Replicatimentioning
confidence: 99%
“…An amino acid mutation that disrupts coat protein binding to the viral RNA (R17A) also blocks RNA replication (37), suggesting that coat protein binding is directly linked to replication functions. The coat protein has also been reported to enhance AMV RNA translation (20); however, the mechanism is not known.…”
mentioning
confidence: 99%
“…Conversely, animal flaviviruses have only a 59-cap; however, PABP interacts with an internal sequence in their 39 UTRs and this enhances translation (Polacek et al 2009). Plant ilarviruses also do not contain poly(A) tails; however, their capsid protein binds to both a 39-proximal RNA element and eIFs associated with their 59-cap, thereby mimicking the translation-enhancing functions of PABP (Neeleman et al 2001;Krab et al 2005). Tobamo-and tymoviruses contain 59-caps but possess tRNA-like structures for 39 termini (Dreher 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with other members of the Bromoviridae family, it has been shown that BMV and Cucumber mosaic virus (CMV) 1a protein accumulates to larger amounts than the corresponding 2a protein in purified replication complexes [35][36][37] , in spite that the SGF total for BMV was 1:2:3 for barley and 1:2:2 for wheat, suggesting that either trans elements are controlling the translation of viral RNAs or that cis-acting elements may affect the efficiency of each RNA in recruiting ribosomes. In this sense, it has been observed that AMV CP enhances the translational efficiently of viral RNAs in vivo 38 via the interaction with the 3′ termini, which adopts two alternative structures for translation (a linear array of hairpins with high affinity for CP) and replication (a pseudo-knotted structure) 39 . A similar mechanism has been reported as regulator for translation of the replication complex proteins of BMV 40 .…”
Section: Discussionmentioning
confidence: 99%